An improved methodology for estimating critical power from mean maximal power output data - Spragg, J.; Leo, P.; Swart, J. (Journal of Sports Sciences, 2023)
The aim of this study was to determine if Critical Power (CP) and W' can be estimated from mean maximal power output (MMP) data collected in cycling races. Data were collected from 13 under 23 professional cyclists (mean ± SD; age, 19.5 ± 1.1 y; body mass, 66.3 ± 5.0 kg; height, 180.0 ± 5.0 cm; CP, 5.7 ± 0.3 W · kg-1). Participants conducted a CP test in the field to determine CPTest and W'Test. MMP data were then collected in races for the subsequent 90 days. CP and W' were estimated from MMP values in two ways, using fixed MMP durations, 2, 5 and 12 min (CPFixed and W'Fixed), and via a novel filtering of second-by-second MMP data (CPFiltered and W'Filtered). CPFixed and CPFiltered were not significantly different from CPTest (Mean Difference (MD) 5 W and 7 W, respectively, p > 0.05). W'Fixed and W'Filtered were not significantly different from W'Test (MD 2.68 kJ and 0.89 kJ, respectively, p > 0.05). CPFixed and CPFiltered correlated significantly with CPTest (r = 0.872 and 0.922, respectively, p < 0.0001 for both). Neither W'Fixed nor W'Filtered correlated significantly with W'Test (p > 0.05). Both CPFixed and CPFiltered provide valid estimates of CPTest.; however, CPFiltered provides a better estimate.